Los miedos infantiles y el rendimiento académico en los niños del nivel de inicial 2 paralelo “c” del centro de educación inicial Lic. “Alfonso Chávez”, parroquia Lizarzaburu, cantón Riobamba, provincia de Chimborazo. Año lectivo 2014-2015 - Caicedo Ayoví, Carlos Javier (2016)
This project is related to childhood fears and academic performance in children, offering teachers and parents, useful tools that will benefit in the future to the little children in the Early Education Center “Alfonso Chavez” to evercome their fear and at the same time improve their academic performance. The theme of the project has much significance, since fears are normal in humans during their lives; but it they fail to contrast to certain ages can be a trigger of many problems. The initiative was taken to conduct this research, with the overall objective: to determine the incidence of childhood fears and academic performance in children Initial Level 2 class, “C” in the Initial Education Center Lic. “Alfonso Chavez,” in parish Lizarzaburu, Riobamba County, Chimborazo province. 2014-2015 school year; by means of the execution of fieldwork, applying the survey to the tearchers, and the observaton in children. As a solution to the ploblem is a teaching guide designed in order to overcome fears of children of that institution and contribute to improved academic performance called “Overcoming my fears I,m happy.” The results allowed to reach the objectives of the investigation, leading to the hypothesis in a positive way because the teachers agreed that significantly affect fears in the academic performance of children. Finally, conclusions are presented and recommendations.